Impact of transversus abdominis plane blocks versus non-steroidal anti-inflammatory on post-operative opioid use in ERAS ovarian cancer surgery. Issue 9 (11th September 2019) - Bisch, Steven Peter; Kooy, Joni; Glaze, Sarah; Cameron, Anna; Chu, Pamela; Ghatage, Prafull; Nation, Jill; Nelson, Gregg; Fitzmaurice, Garrett M
Abstract : Background: Treatment of ovarian cancer often requires extensive surgical resection. The transversus abdominis plane (TAP) block has been utilized in benign gynecologic surgery to decrease post-operative pain and opioid use. We hypothesized that TAP blocks would decrease total opioid use in the first 24 hours and decrease length of stay following staging and cytoreductive surgery for ovarian cancer compared with either no local anesthetic or local wound infiltration alone. Methods: All patients undergoing surgery for ovarian cancer from November 2016 to June 2017 were included in this retrospective cohort study. Median opioid use at 24, 48, and 72 hours post-operatively, as well as length of stay, were assessed. Multivariate median regression analysis was performed to adjust for potential confounders: post-operative non-steroidal anti-inflammatory drug (NSAID) usage, pre-operative opioid consumption, and extent of cytoreductive surgery. Length of stay was compared using Cox regression analysis. Results: One-hundred-and-twenty patients were included in the analysis. Eighty-two patients had a TAP block, while 38 did not. After adjusting for potential confounders there was no difference in median 24 hours opioid consumption (p=0.29) or length of stay (HR 0.95, p=0.78) between patients receiving TAP block compared with those without. After adjusting for potential confounders, patients receiving scheduled NSAIDs had a 2.6-fold greater likelihood of being discharged (p<0.0005) and a significant reduction in median opioid use at 24 hours (23.5 vs 14.5 mg) (p=0.017) compared with those patients without NSAIDs. Discussion: Post-operative administration of NSAIDs, but not TAP block, was associated with a decrease in post-operative opioid use and length of stay following surgery for ovarian cancer. Further investigation into alternative regional anesthetics for Enhanced Recovery after Surgery (ERAS) protocols is warranted.